Characterization of Wolinella spp., Campylobacter concisus, Bacteroides gracilis, and Eikenella corrodens by polyacrylamide gel electrophoresis. - Tanner, A C (1986)
The small asaccharolytic, nonpigmenting gram-negative rods of the human oral cavity are difficult to differentiate from each other. Protein profiles of sonicated cells of Wolinella species, Campylobacter concisus, Bacteroides gracilis, and Eikenella corrodens were obtained by sodium dodecyl sulfate-polyacrylamide gel electrophoresis and visualized with a silver stain. The gels were scanned with a laser densitometer, and the similarity of strains was computed by determining correlation coefficients of normalized densities along the gels. The strains were grouped by cluster analysis of the correlation coefficients. All species were distinct from each other. Several groups were found within E. corrodens. A colored silver stain was found to highlight species differences and appears to be useful in the rapid identification of fresh isolates.